Synthesis and In vitro Evaluation of Doxorubicin loaded Polymeric Nanoparticles on Cancer Cells: Synthesis and In vitro Evaluation of Doxorubicin loaded Polymeric Nanoparticles - Nimra Batool; Tayyaba Saif; Tahira Anwar; Sajjad Ullah; Sikandar Hayat; Malik Ihsan Ullah Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Cancer is the second biggest mortality rate globally. Most of anti-cancer drugs are hydrophobic and when they are administered in the body, they get clear from the blood. That’s why polymeric nanoparticles (NPs) have been used for delivering anti-cancer drugs to targeted sites. Biodegradable and self-assembled nature, PEG-PLGA has been used as a nanocarrier for biomedical applications. We developed PEG-PLGA NP for the doxorubicin (DOX) delivery to cancerous cells. The successful PEG-PLGA synthesis was confirmed by its 1 H NMR spectrum. All NPs displayed individual spherical morphology and 100 nm size range with -18.5mV zeta potential. Drug release profile showed DOX had sustained release pattern from DOX@NPs. In vitro, MTT assay and apoptosis analysis revealed that low-dose DOX@NPs exhibited more toxic effects on cancerous cells as compared to DOX alone. Overall results demonstrate that polymeric-based nanosystems increase the efficacy of DOX on cancer cells.